Anonim Anonim 08-04-2020 Matematică a fost răspuns 20.13. Rezolvaţi în mulțimea numerelor reale ecuațiile:a) 7(x + 2) - 2(x - 4) = 6(x + 2) - 9; b) 10(x - 1)-3(4x – 7) - 2 = 4(3x – 5) +1:c) 3(2x - 7) - 5(x - 2) - 3 = 2(x - 7) + 7; d) 4(x - 5) + 3(3x - 5) = 2(2x + 5) - 9;e) 5(2x + 1) - 8(1 - x) = 2(3x + 2) + 5; f) 3(5 + 4x) - 6(x + 2) = 5(2x - 1) -4;g) 18(2 - x) + 6(7x - 12) = 5(2x - 1) - 3; h) 2(3x + 4) – 5(2x - 3) = 7(x – 3) +11;i) 4(9x – 4) - 3(3x - 10) + 11 = 4(2x - 21) - 5;j) 2(5x - 4)+6(4x – 3) +11 = 6(3x – 4) – 7.VA ROG